Kano Model applied to the evaluation a collaborative board game for teaching in environmental education - Parreiras, Marcus; Marques, Pedro; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2022.226092, 2022)
This article discusses the application of the Kano Model to a collaborative educational board game focused on environmental sustainability. A satisfaction survey was conducted according to the model. The results point to a general satisfaction of the players towards the game’s attributes. Analyzing the results, the Kano Model offers an excellent option to analyze the attributes of a game from the perspective of the players as a product, and can be a useful tool to understand players and position efforts for better results in future projects.